Comparative proteomic analysis reveals that T3SS, Tfp, and xanthan gum are key factors in initial stages of Citrus sinensis infection by Xanthomonas citri subsp citri - Facincani, Agda P. [UNESP]; Moreira, Leandro M.; Soares, Marcia R.; Ferreira, Cristiano B. [UNESP]; Ferreira, Rafael M. [UNESP]; Ferro, Maria I. T. [UNESP]; Ferro, Jesus A. [UNESP]; Gozzo, Fabio C.; Oliveira, Julio C. F. de (Springer, 2014)
The bacteria Xanthomonas citri subsp. citri (Xac) is the causal agent of citrus canker. The disease symptoms are characterized by localized host cell hyperplasia followed by tissue necrosis at the infected area. An arsenal of bacterial pathogenicity- and virulence-related proteins is expressed to ensure a successful infection process. At the post-genomic stage of Xac, we used a proteomic approach to analyze the proteins that are displayed differentially over time when the pathogen attacks the host plant. Protein extracts were prepared from infectious Xac grown in inducing medium (XAM1) for 24 h or from host citrus plants for 3 or 5 days after infection, detached times to evaluate the adaptation and virulence of the pathogen. The protein extracts were proteolyzed, and the peptides derived from tryptic digestion were investigated using liquid chromatography and tandem mass spectrometry. Changes in the protein expression profile were compared with the Xac genome and the proteome recently described under non-infectious conditions. An analysis of the proteome of Xac under infectious conditions revealed proteins directly involved in virulence such as the type III secretion system (T3SS) and effector proteins (T3SS-e), the type IV pilus (Tfp), and xanthan gum biosynthesis. Moreover, four new mutants related to proteins detected in the proteome and with different functions exhibited reduced virulence relative to the wild-type proteins. The results of the proteome analysis of infectious Xac define the processes of adaptation to the host and demonstrate the induction of the virulence factors of Xac involved in plant-pathogen interactions.
Keywords: Citrus canker; Plant-pathogen interaction; Xanthan gum; T3SS; Tfp